Research on Assessment Method of Sediment Pollution in River and Lake - HUANG Senjun; ZHOU Yan; RONG Hua; ZHANG Ge (Renmin Zhujiang)
Sediment pollution is one of the main reasons for deterioration of urban water environment, and sediment pollution assessment is of great significance for the selection of in-situ or ex-situ treatment. This paper discusses and summarizes the pollution assessment methods for heavy metal, organic matter and polycyclic aromatic hydrocarbons (PAHs) respectively, and compares and analyzes the advantages and disadvantages of the assessment methods for heavy metal pollution based on the column data of Maozhou River, which will provide valuable reference and technical support for sediment pollution control.